Indoor and outdoor PM10 levels at schools located near mine dumps in Gauteng and North West Provinces, South Africa - Vusumuzi Nkosi; Janine Wichmann; Kuku Voyi (BMC, 2017)
Abstract Background Few studies in South Africa have investigated the exposure of asthmatic learners to indoor and outdoor air pollution at schools. This study compared outdoor PM10 and SO2 exposure levels in exposed (1-2 km from gold mine dumps) and unexposed schools (5 km or more from gold mine dumps). It also examined exposure of asthmatic children to indoor respirable dust at exposed and unexposed schools. Methods The study was conducted between 1 and 31 October 2012 in five schools from exposed and five from unexposed communities. Outdoor PM10 and SO2 levels were measured for 8-h at each school. Ten asthmatic learners were randomly selected from each school for 8-h personal respirable dust sampling during school hours. Results The level of outdoor PM10 for exposed was 16.42 vs. 11.47 mg.m−3 for the unexposed communities (p < 0.001). The outdoor SO2 for exposed was 0.02 ppb vs. 0.01 ppb for unexposed communities (p < 0.001). Indoor respirable dust in the classroom differed significantly between exposed (0.17 mg.m−3) vs. unexposed (0.01 mg.m−3) children with asthma at each school (p < 0.001). Conclusion The significant differences between exposed and unexposed schools could reveal a serious potential health hazard for school children, although they were within the South African Air Quality Standards' set by the Department of Environmental Affairs. The indoor respirable dust levels in exposed schools could have an impact on children with asthma, as they were significantly higher than the unexposed schools, although there are no published standards for environmental exposure for children with asthma.